the problem 7x^2+123x-4

The quadratic formula assumes you have a quadratic equation equal to zero. In general: ax^2 + bx + c = 0.

In this case, 7x^2 + 123x - 4 = 0, so a = 7, b = 123, and c = -4 (c is negative because the standard form

assumes a, b, and c are positive).

Now, we can use the quadratic formula: x = [-b ± √(b^2-4ac)] / 2a

With a = 7, b = 123, and c = -4, x is equal to [-123 ± √(123^2-4(7)(-4)]/ 14 ≈ .03 and -17.60 when you simplify. There are two solutions because you have to do plus AND minus the square root.